Allometric association between physical fitness test results, body size/shape, biological maturity, and time spent playing sports in adolescents. - Matteo Giuriato; Adam Kawczynski; Dariusz Mroczek; Nicola Lovecchio; Alan Nevill (PLoS ONE)
Regular participation in strength and conditioning activities positively correlates with health-related benefits in sports (team and individual). Maturity offset (MO) is a recognized parameter in fitness outcome assessment. The aims of the present study are to analyze cross-sectional allometric development of motor performances in a sample of adolescents and relate scaled motor performance to the estimated amount and type of physical activity and biological maturity status in 771 subjects aged 14-19 years. Three physical fitness components were evaluated using field tests (standing broad jump, sit-ups, shuttle run). Extra hours of sport after school (EHS) and MO were the covariates. The model to predict the physical performance variables was: Y = a · Mk1 · Hk2 · WCk3 · exp(b · EHS + c · MO) · ε. Results suggest that having controlled for body size and body shape, performing EHS and being an early developer (identified by a positive MO slope parameter) benefits children in physical fitness and motor performance tasks.